Peran Insentif, Perilaku Kepemimpinan, dan Budaya Organisasi terhadap Penguatan Komitmen Organisasi - Jahroni Jahroni; Didit Darmawan; Rahayu Mardikaningsih; Ella Anastasya Sinambela (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
This study intends to find out about the truth that incentives given to employees, effective leadership behavior, and existing organizational culture are thought to have a role in strengthening organizational commitment. The survey is conducted in the production department of a company. Respondents consist of active employees who work at PT. KJA which has 43 employees in the production department. The sampling technique is by census. Regression model, t test, and F test are SPSS-assisted analytical tools. The results showed that incentives, leadership behavior, and organizational culture were proven to have a role in strengthening organizational commitment